2014
DOI: 10.1016/j.hrthm.2013.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Device artifact reduction for magnetic resonance imaging of patients with implantable cardioverter-defibrillators and ventricular tachycardia: Late gadolinium enhancement correlation with electroanatomic mapping

Abstract: Background Late Gadolinium Enhancement (LGE) MRI of ventricular scar has been shown to be accurate for detection and characterization of arrhythmia substrates. However, the majority of patients referred for ventricular tachycardia (VT) ablation have an implantable cardioverter defibrillator (ICD), which obscures image integrity and the clinical utility of MRI. Objective To develop and validate a wideband LGE MRI technique for device artifact removal. Methods A novel wideband LGE MRI technique was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 17 publications
1
52
1
1
Order By: Relevance
“…The presence of an implantable cardioverter defibrillator (ICD) is still a contraindication to MRI. However, in the future such patients could benefit from the development of MR-conditional implants under certain conditions [73].…”
Section: Mr-guided Cardiac Ablationmentioning
confidence: 99%
“…The presence of an implantable cardioverter defibrillator (ICD) is still a contraindication to MRI. However, in the future such patients could benefit from the development of MR-conditional implants under certain conditions [73].…”
Section: Mr-guided Cardiac Ablationmentioning
confidence: 99%
“…Вместе с тем, существуют определенные сложности проведения интервенционного вмеша-тельства, поскольку местоположения циклов ри-ентри и характеристики ЖТ значительно варьируют из-за трехмерной геометрии инфарктных областей. Это ассоциировано с размером, глубиной поражения, трансмуральной дисперсией рефрактерности и гео-метрией миокардиального рубца после острого ИМ (ОИМ) [3,4]. К тому же, проведение радиочастотной аблации (РЧА) ограничено при неустойчивых, гемо-динамически значимых и неиндуцируемых тахикар-диях.…”
Section: клинические и структурно-электрофизиологические предикторы рunclassified
“…Artifactual myocardial hyperintensity on late gadolinium enhancement images may potentially mimic infarct or fibrosis when the resonant frequency offset caused by the metal of the device generator exceeds the bandwidth of the inversion pulse. Rashid et al 12 and Stevens et al 13 showed that by simply increasing the bandwidth of the inversion recovery pulse, the inversion became much more uniform in the face of local field inhomogeneities, and the artifact was reduced. A wideband inversion pulse was also shown to be successful in reducing artifacts in late gadolinium enhancement imaging of patients with ICDs scanned at 3.0T, 14 where the local susceptibility gradients surrounding a metallic implant are twice what they are at 1.5T.…”
Section: See Article By Schwitter Et Almentioning
confidence: 99%